Endoplasmic reticulum membrane protein MoScs2 is important for asexual development and pathogenesis of Magnaporthe oryzae - Zhang, Jun; Chen, Xuehang; Yang, Zifeng; Xu, Huxiao; Weng, Shuning; Wang, Zonghua; Tang, Wei (Frontiers in Microbiology, 2022)
Most secretory proteins are folded and modified in the endoplasmic reticulum (ER). In Saccharomyces cerevisiae, the absence of Scs2 protein will lead to the separation of the endoplasmic reticulum and plasma membrane, resulting in endoplasmic reticulum dysfunction, but its function is not clear in rice blast fungus or even filamentous fungus. In this study, we report the identification and characterization of MoSCS2 in the pathogenesis of the rice blast fungus Magnaporthe oryzae. Protein subcellular localization showed that MoSCS2 is mainly localized in the endoplasmic reticulum. Compared to the wild-type strain Guy11, the deletion mutant Moscs2 showed a significant reduction in growth and conidiation. MoSCS2 deficiency also resulted in abnormal conidial morphology and septum formation. The ΔMoscs2 mutant shows delayed appressorium formation, and the appressorium of ΔMoscs2 mutant couldn't form huge turgor pressure to penetrate the host epidermal cell wall. Pathogenicity and plant leave infection assays showed that knockout of MoSCS2 significantly inhibited the expansion of the invasive hyphae in host cells, ultimately leading to the decline of pathogenicity. Moreover, MoSCS2 gene is also involved in the regulation of cell wall and endoplasmic reticulum stress response. In conclusion, MoSCS2 plays an important role in the growth, asexual production, conidia morphogenesis, infection-related morphogenesis and pathogenicity of M. oryzae.